Tomographic Imaging of the Sagittarius Spiral Arm's Magnetic Field Structure - Yasuo Doi; Kengo Nakamura; Koji S. Kawabata; Masafumi Matsumura; Hiroshi Akitaya; Simon Coudé; Claudia V. Rodrigues; Jungmi Kwon; Motohide Tamura; Mehrnoosh Tahani; Antonio Mario Magalhães; Reinaldo Santos-Lima; et al. (The Astrophysical Journal, 2024)
The Galactic global magnetic field is thought to play a vital role in shaping Galactic structures such as spiral arms and giant molecular clouds. However, our knowledge of magnetic field structures in the Galactic plane at different distances is limited, as measurements used to map the magnetic field are the integrated effect along the line of sight. In this study, we present the first ever tomographic imaging of magnetic field structures in a Galactic spiral arm. Using optical stellar polarimetry over a $17^{′} × 10^{′} $ field of view, we probe the Sagittarius spiral arm. Combining these data with stellar distances from the Gaia mission, we can isolate the contributions of five individual clouds along the line of sight by analyzing the polarimetry data as a function of distance. The observed clouds include a foreground cloud ( d < 200 pc) and four clouds in the Sagittarius arm at 1.23, 1.47, 1.63, and 2.23 kpc. The column densities of these clouds range from 0.5 to 2.8 × 10 ^21 cm ^−2 . The magnetic fields associated with each cloud show smooth spatial distributions within their observed regions on scales smaller than 10 pc and display distinct orientations. The position angles projected on the plane of the sky, measured from the Galactic north to the east, for the clouds in increasing order of distance are 135°, 46°, 58°, 150°, and 40°, with uncertainties of a few degrees. Notably, these position angles deviate significantly from the direction parallel to the Galactic plane.